What’s Hot at CPAIOR (Extended Abstract) - Quimper, Claude-Guy (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
The 13th International Conference on Integration of Artificial Intelligence and Operations Research Techniques in Constraint Programming (CPAIOR 2016), was held in Banff, Canada, May 29 - June 1, 2016. In order to trigger exchanges between the constraint programming and the operations research community, CPAIOR was co-located with CORS 2016, the Canadian Operational Research society’s conference.